The Influence of Inner Component and Topographical Properties on Tribological Parameters of Injection-Moulded Microparts. (28th October 2014) - Fischer, Christopher; Drummer, Dietmar
Abstract : Tribological parameters are dependent upon inter alia, inner component properties which may vary with the temperature-time behaviour of the polymer melt used. This temperature-time behaviour can be influenced by dynamic mould temperature control. The present paper presents a new dynamic tempering concept, which enables a targeted temperature-time control via shifting a mould cavity within two different tempered mould areas at a defined point in time. By influencing the temperature-time development by means of a mould temperature and isothermal holding time variation, micro tensile bars with different inner component properties are produced. To show the influence of inner component properties on tribological parameters, pin-on-disc wear tests are performed. Furthermore, tribological tests with different surface topographies are performed to show the influence of topographical properties on tribological parameters. Results indicate that the tribological properties of microparts are mainly influenced by the nature of the skin near layers, which can be influenced by the application of different mould temperatures. Variations in the isothermal holding time show no significant impact on the material examined. A more distinct roughness of the disc surface topography not only shows higher values for the measured tribological parameters but also different wear behaviour in general.